Kinetics of Ethanol and Acetaldehyde Release Suggest a Role for Acetaldehyde Production in Tolerance of Rice Seedlings to Micro-aerobic Conditions - BOAMFA, E. I. (Ann Bot, 2005)
• Background and Aims This paper examines the basis of the greater tolerance of an indica rice cultivar FR13A to complete submergence compared with relatively intolerant japonica rice CT6241. We study whether this superior tolerance is related to its greater tolerance to O(2) shortage and to an ability to run a more favourable rate of alcoholic fermentation during and after O(2) deprivation. • Methods Fermentation products were analysed using sensitive laser-based photoacoustics at high time resolution to establish patterns and rates of ethanol and acetaldehyde emission by intact rice seedlings exposed to micro-aerobic (0·05–0·5 % O(2)) or zero O(2) supply, and also during their return to air. Oxygen and CO(2) emission or uptake was also quantified. • Key Results In the dark, no acetaldehyde and ethanol emission was observed until external O(2) concentration in a gas phase decreased to ≤0·3 % O(2). The ethanol production rate was maximal in 0 % O(2), similar in both cultivars and gradually diminished with increasing O(2) concentration. Lag time for induction of fermentation increased with O(2) up to 0·3 % and was shorter in CT6241. Light strongly suppressed fermentation. In contrast to that of ethanol, emission of acetaldehyde in the dark under micro-aerobic conditions (≤0·15 % O(2) gas phase) exceeded that under anaerobiosis, was maximal in 0·05 % O(2) and was greater in FR13A than in CT6241. A drop in acetaldehyde emission to about half its value immediately followed a switch to anaerobic conditions after 6·5 h treatment under 0·05 % O(2), while ethanol release showed a further increase. A large peak in acetaldehyde emission immediately followed the return of seedlings to air after treatment with ≤0·15 % O(2). The emission from FR13A was up to three times larger than from CT6241. • Conclusions Tolerance to submergence in FR13A appears not to be connected to its rate of ethanol production during anaerobiosis, but to the increased acetaldehyde output during and after experiencing micro-aerobic conditions (0·05–0·15 % O(2)). Extra acetaldehyde production from ethanol may be a consequence of diversion of the reactive oxygen species away from the damaging lipid peroxidation pathway.